Effect of sunflower stover and nutrients management on productivity, nutrient economy and phosphorus use efficiencies of pigeonpea (Cajanus cajan)-sunflower (Helianthus annuus) cropping system - BABU, SUBHASH; RANA, D S; PRASAD, DASHARATH; PAL, SURESH (The Indian Journal of Agricultural Sciences, 2013)
A fixed plot field experiment was carried out during kharif and spring seasons of 2008–09 and 2009–10 at Researchfarm of Division of Agronomy, Indian Agricultural Research Institute, New Delhi, to study the effect of sunflower stoverand nutrients management on productivity, nutrient economy and phosphorus use efficiencies of pigeonpea (Cajanuscajan)-sunflower (Helianthus annuus) cropping system. In 2008–09, sunflower stover incorporation caused 6.17, 6.05,4.90 and 5.1 percent increment in system productivity, production efficiency, per day returns and net returns over nostover incorporation, respectively. However, sunflower stover incorporation was failed to affect the system productivityand production efficiency during the second year of experimentation. Application of 30 kg P/ha to pigeonpea recorded maximum system productivity (4.17 and 3.24 tonnes/ha), production efficiency (11.42 and 8.88 kg/ha/day), net returns (Rupees 72.8 and 71.6x103/ha), per day returns (199 and 196 Rupees/ha) during 2008–09 and 2009–10, respectively. Recommended dose (RD) of NP applied directly to sunflower produced the markedly higher productivity (3.18 t/ha), production efficiency(8.71 kg/ha/day) net returns Rupees,69.1x103/ha and per day returns (189 Rupees/ha). Residual effect of 8 tonnes/ha sunflower stover incorporation and 30 kg/ha P was significant on nutrient economy of succeeding sunflower crop and reduced up to 50% recommended dose of P. Direct effect of sunflower stover incorporation had significant effect on agronomic P use efficiency (APUE), agro physiological P use efficiency (APPUE), physiological efficiency index of P (PEIP) during 2009 only, while residual effect of sunflower stover incorporation significantly affected the agronomic P use efficiency (APUE), physiological efficiency index of P (PEIP) during both the years and agro physiological P use efficiency (APPUE) only during 2009. With regards to the direct and residual effect of P levels, the direct effect of 15 kg P/ha+PSB recorded the higher values of APUE during both the years. However, the maximum values of APPUE and PEIP recorded with the direct effect of 15 kg P/ha. The residual effect of P levels applied to preceding pigeonpea crop showed perceptible reduction in APPUE during both years of study, and APUE in 2009 and PEIP during 2010 with successive increment of P levels. Direct effect of 50% RD of NP had marked increase of APUE and APPUE, over control and RD of NP. In contrast and PEIP reduced with successive doses of NP up to RD of NP. The residual effect of RD of NP applied to preceding sunflower crop recorded the minimum values of APUE, APPUE and PEIP in pigeonpea.